2023
DOI: 10.3390/ijms24043781
|View full text |Cite
|
Sign up to set email alerts
|

The Strategies of Development of New Non-Toxic Inhibitors of Amyloid Formation

Abstract: In recent years, due to the aging of the population and the development of diagnostic medicine, the number of identified diseases associated with the accumulation of amyloid proteins has increased. Some of these proteins are known to cause a number of degenerative diseases in humans, such as amyloid-beta (Aβ) in Alzheimer’s disease (AD), α-synuclein in Parkinson’s disease (PD), and insulin and its analogues in insulin-derived amyloidosis. In this regard, it is important to develop strategies for the search and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 201 publications
(221 reference statements)
0
3
0
Order By: Relevance
“…8,9 They rely primarily on the design of small molecules or antibodies that bind to monomeric or aggregated protein species, thereby making the substrate unavailable for conversion 10 and/or sterically interfering with the aggregation process. 9,[11][12][13] Traditional small molecule drugs and protein-based therapeutics have made good contributions, yet their limitations in terms of selectivity, stability, and bioavailability, 14,15 as well as their repeated failure in clinical trials 16,17 have inspired the search for alternative therapeutic approaches. Among these, peptides and particularly cyclic peptides are attracting considerable attention due to their unique structural properties and diverse biological activities.…”
Section: Ioana M Iliementioning
confidence: 99%
See 1 more Smart Citation
“…8,9 They rely primarily on the design of small molecules or antibodies that bind to monomeric or aggregated protein species, thereby making the substrate unavailable for conversion 10 and/or sterically interfering with the aggregation process. 9,[11][12][13] Traditional small molecule drugs and protein-based therapeutics have made good contributions, yet their limitations in terms of selectivity, stability, and bioavailability, 14,15 as well as their repeated failure in clinical trials 16,17 have inspired the search for alternative therapeutic approaches. Among these, peptides and particularly cyclic peptides are attracting considerable attention due to their unique structural properties and diverse biological activities.…”
Section: Ioana M Iliementioning
confidence: 99%
“…[3][4][5][6][7] Various approaches have been developed to interfere with the accumulation processes by stabilizing or eliminating specific monomeric or aggregated forms of the responsible polypeptides. 8,9 They rely primarily on the design of small molecules or antibodies that bind to monomeric or aggregated protein species, thereby making the substrate unavailable for conversion 10 and/or sterically interfering with the aggregation process. 9,[11][12][13] Traditional small molecule drugs and protein-based therapeutics have made good contributions, yet their limitations in terms of selectivity, stability, and bioavailability, 14,15 as well as their repeated failure in clinical trials 16,17 have inspired the search for alternative therapeutic approaches.…”
Section: Ioana M Iliementioning
confidence: 99%
“…Research has been done on many different variants of natural products which have shown increasing potential in inhibiting the formation of amyloid fibrils in vitro. 20 The most widely studied natural products which have been documented include epigallocatechin gallate (EGCG), 21 resveratrol 22 and curcumin. 23 These small polyphenolic compounds show remarkable inhibition of the formation of fibrillar assemblies in vitro.…”
Section: Introductionmentioning
confidence: 99%